2020
DOI: 10.3389/fpls.2020.00709
|View full text |Cite
|
Sign up to set email alerts
|

A Novel AP2/ERF Transcription Factor, OsRPH1, Negatively Regulates Plant Height in Rice

Abstract: The APETALA 2/ethylene response factors (AP2/ERF) are widespread in the plant kingdom and play essential roles in regulating plant growth and development as well as defense responses. In this study, a novel rice AP2/ERF transcription factor gene, OsRPH1, was isolated and functionally characterized. OsRPH1 falls into group-IVa of the AP2/ERF family. OsRPH1 protein was found to be localized in the nucleus and possessed transcriptional activity. Overexpression of OsRPH1 resulted in a decrease in plant height and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…OsERF83 OX plants showed growth retardation and low grain yields ( Figure 3 , Figure S5, Table S1 ). Generally, plants exhibiting stress tolerance have been reported to show growth retardation [ 30 , 31 ] because of hypersensitivity in responding to stresses, directing resources to protection from stresses rather than growing or yielding, which is known as a trade-off. Thus, genes improving stress tolerance induce growth retardation under normal growth conditions when they are constitutively overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…OsERF83 OX plants showed growth retardation and low grain yields ( Figure 3 , Figure S5, Table S1 ). Generally, plants exhibiting stress tolerance have been reported to show growth retardation [ 30 , 31 ] because of hypersensitivity in responding to stresses, directing resources to protection from stresses rather than growing or yielding, which is known as a trade-off. Thus, genes improving stress tolerance induce growth retardation under normal growth conditions when they are constitutively overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…TA transactivation activity assay was performed according to the manufacturer's protocol (Clontech). The plasmid pBridge-OsWRKY50 was transformed into the yeast strain Y2HGold, in addition, pBridge-OsRPH1 was used as a positive control [32], and the empty vector pBridge was used as a negative control. Then, the transformants grown on a single-dropout media (SD/-Trp) were subcultured on double-dropout media (SD/-His/-Trp).…”
Section: Transactivation Activity and Yeast One-hybrid (Y1h) Assaysmentioning
confidence: 99%
“…Furthermore, Kavas et al indicated higher expression levels of PvAP2-ERF111, PvAP2-ERF119, PvAP2-ERF72, and PvAP2-ERF150 genes in common bean leaf tissues after salt treatment, suggesting the involvement of these genes in salt stress signal transduction [35]. Ma et al identified a novel AP2/ERF gene from rice, OsRPH1, that negatively controls plant height [36]. Additionally, a novel ERF gene, ZmERF105, was isolated from maize that positively controls resistance to Exserohilum turcicum [37].…”
Section: Introductionmentioning
confidence: 99%